2021
DOI: 10.1007/s00103-021-03415-9
|View full text |Cite
|
Sign up to set email alerts
|

Adhärenz digitaler Interventionen im Gesundheitswesen: Definitionen, Methoden und offene Fragen

Abstract: ZusammenfassungViele digitale Interventionen sind auf die Mitwirkung ihrer Nutzer*innen angewiesen, damit sie eine positive Wirkung erzielen können. In verschiedenen Bereichen ist zu beobachten, dass die Anwendung digitaler Interventionen durch Nutzer*innen oftmals nach einer kurzen Zeit reduziert oder in Gänze eingestellt wird. Dies wird als einer der wesentlichen Faktoren angesehen, der die Wirksamkeit digitaler Interventionen einschränken kann. In diesem Zusammenhang gewinnt das Konzept der Adhärenz (Einhal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
0
7
0
4
Order By: Relevance
“…The literature review revealed that technology-based interventions are often associated with low adherence and high dropout rates. To increase acceptance and motivation to use the intervention and ensure better intervention outcomes, users should be involved in all phases of intervention development (Alberts et al, 2020; Kernebeck et al, 2021). A participatory development process would enable the assessment of target groups’ needs in order to take them into account during intervention development.…”
Section: Methodsmentioning
confidence: 99%
“…The literature review revealed that technology-based interventions are often associated with low adherence and high dropout rates. To increase acceptance and motivation to use the intervention and ensure better intervention outcomes, users should be involved in all phases of intervention development (Alberts et al, 2020; Kernebeck et al, 2021). A participatory development process would enable the assessment of target groups’ needs in order to take them into account during intervention development.…”
Section: Methodsmentioning
confidence: 99%
“…Informationen aus der digitalen Anwendung können Teil des Arztgesprächs und der Therapieanpassung werden. Dies kann Betroffene zur dauerhaften Nutzung motivieren [39]. Ein weiterer Vorteil wäre, dass die Skepsis gegenüber DiGA auf Seiten der Leistungserbringer abgebaut werden könnte.…”
Section: Diskussionunclassified
“…Allerdings ist der Nutzen eng an die tatsächliche Nutzung der Anwendung gekoppelt. Ohne Überwachung durch Leistungserbringer kann insbesondere bei Patienten mit psychischer Erkrankung eine digitale „Erschöpfung“ entstehen 38 , 39 . In der Folge wird die Anwendung nicht mehr effektiv oder gar nicht mehr genutzt und es kann kein positiver Versorgungseffekt erreicht werden 38 , 39 .…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Adherence e concept of adherence to digital interventions is roughly de ned as the degree to which the user followed the program as it was designed, which can also be paraphrased as "intended use" or "use as it is designed" (57). Adherence to the digital physiotherapy intervention will be automatically recorded by the app, in compliance with the scheduled sessions.…”
Section: Secondary Explanatory Outcomesmentioning
confidence: 99%